Amiodarone-related pneumonitis and peripheral neuropathy in an elderly patient - Rosseti, Nirmala (Aging Clin Exp Res, 2013)
Amiodarone, which has been used since 1967 as an antiarrhythmic drug, gives rise to a variety of cardiac and extracardiac adverse side-effects. Among these, pulmonary toxicity is considered the most frequent and serious extracardiac side-effect, since it may occur in various atypical forms and often limits the drug’s clinical use. We encountered a 67-year-old white male patient with suspected amiodarone pneumonitis characterized by multiple lung nodules associated with pleural and pericardial effusion and peripheral neuropathy. Because differential diagnosis with pulmonary infectious diseases may be extremely difficult, the attending physician should therefore bear in mind the possibility of amiodarone pneumonitis whenever the drug is given.